The Effect of Nutrition Education on Glycemic Outcomes in People With Type 1 Diabetes Initiating the Use of Glucose Sensors - Navrátilová, Vendula; Zadáková, Eliška; Šoupal, Jan; Škrha, Jan; Do, Quoc Dat; Radovnická, Lucie; Hásková, Aneta; Prázný, Martin; Horová, Eva (Endocrinology, diabetes & metabolism, 2025)
AIM: To determine whether people with type 1 diabetes (T1D) initiating glucose sensor monitoring experience greater improvements in HbA1c when provided with education on carbohydrate counting and flexible insulin dosing than those who do not receive nutrition education. MATERIALS AND METHODS: Our retrospective observational study included 329 people with T1D initiating glucose sensor monitoring between 2015 and 2021. The participants were divided into two groups: one group attended at least one structured educational session with a registered dietitian (n = 126), while the other group did not receive structured education (n = 203). After 12 months of glucose sensor initiation, we compared glycaemic outcomes and CGM metrics between the two groups. RESULTS: At glucose sensor initiation, both groups with and without education had similar HbA1c levels (7.64% [60.0 mmol/mol] vs. 7.66% [60.2 mmol/mol]). After twelve months, the education group demonstrated greater improvement in glycemic outcomes (HbA1c 7.17% [54.9mmol/mol] vs. 7.37% [57.1 mmol/mol], p < 0.05) and spent significantly more time in the target range than did the group without structured education (68.8% vs. 64.1%, p < 0.05). We observed an inverse correlation between the number of completed educational sessions and HbA1c after 12 months, as well as between the number of educational sessions and the change in HbA1c. CONCLUSIONS: People with T1D who initiated glucose sensor monitoring alongside nutrition education showed greater improvements in HbA1c and increased time spent in the target glucose range compared to individuals who did not receive structured education. TRAIL REGISTRATION: ClinicalTrials.gov identifier: NCT06264271.
Keywords: Insulin; diabetes mellitus 1. typu; Male; retrospektivní studie; regulace glykemie; inzulin; selfmonitoring glykemie; glykovaný hemoglobin; krevní glukóza; Adult; dospělí; Blood Glucose Self-Monitoring; mužské pohlaví; Patient Education as Topic; vzdělávání pacientů jako téma; hypoglykemika; lidé; ženské pohlaví; Glycated Hemoglobin; Humans; Glycemic Control; Hypoglycemic Agents; Diabetes Mellitus, Type 1; Retrospective Studies; Female; Blood Glucose; lidé středního věku; Middle Aged